EMPLOYEE PERFORMANCE REVIEWED FROM INITIATIVE, WORK DISCIPLINE, WORK MOTIVATION, AND EMPLOYEE READINESS FOR CHANGE IN THE CENTRAL JAVA II REGIONAL OFFICE OF THE DIRECTORATE GENERAL OF TAXES - Budi Citra Permana; Bambang Mursito; Sarsono Sarsono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The study aims to measure the effect of initiative, work discipline, work motivation, and readiness for change on the employee performance of the Central Java II Regional Office of the Directorate General of Taxes. The research method of this study is quantitative research. Samples use purposive sampling method, that is, sampling method which uses certain considerations. The sample in this study were certain employees of the Central Java II Regional Office of the Directorate General of Taxes, amounting to 120 samples of 152 total population. Data collection is obtained through questionnaires. The data analysis technique uses multiple linear regression analysis. The results showed that (1) initiative variable has a positive and significant effect on employee performance, (2) work discipline variable has no significant effect on employee performance, (3) The work motivation variable has a positive and significant effect on employee performance, (4) The readiness for change variable has a positive and significant effect on employee performance. Keywords: initiative, work discipline, work motivation, readiness for change, performance